Tectonophysical changes in rock mass during hydraulic fracturing (based on the example of the West-Khrestishche brachyanticline structure) - Tkachov , Anton; Serdiukova, Olga (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. Hydraulic fracturing is a technology for creating an artificial compaction zone in a rock mass in order to form compact hydrocarbon accumulations. As a result, radical tectonophysical changes occur in the mass, associated with the emergence of systems of cracks and pores in productive terrigenous strata. The fracture-pore space formed by the action of a water-emulsion solution under high pressure on the rock mass creates a compact compaction zone in which hydrocarbons accumulate. If there are already existing lithogenic and tectogenic fractures and pores in productive formations, the rate of formation of the compaction zone may be accelerated or slowed down. The latter is due to a change in the vector of fluid flow into existing fractures, which reduces the impact-destructive effect of hydraulic fracturing. The properties of the hydraulic fracturing fluid significantly affect the fracture development mode. The viscosity of the process fluid depends on both its molecular weight and the concentration of the polymer it contains. A decrease in the viscosity of the latter indicates that the used fluid can be removed from the fracture by coiled tubing. Objective. Identify tectonophysical changes occurring in rock formations as a result of hydraulic fracturing. To investigate the structural-tectonic and hydrodynamic factors influencing the hydraulic fracturing of sedimentary rocks in the coal complex. Results. Tectonophysical changes occurring as a result of hydraulic fracturing are considered using the example of the West-Khrestishche brachyanticline structure – a fold of sublatitudinal extension in the Upper Carboniferous – Lower Permian deposits. It is located in the development zone in a thick sedimentary sequence of salt dome structures in the southeastern part of the Dnieper-Donets Basin. The geological factors influencing changes in the geological environment during hydraulic fracturing are studied using the example of the West-Khrestishche gas condensate field. A comprehensive analysis of the geological structure, hydrodynamic conditions, and seismic data was conducted. A model of the formation of pore-fracture space as a result of hydraulic fracturing was constructed. Scientific novelty. Using the example of the West-Khrestyshche field, a comprehensive analysis of the impact of various factors on changes in the geological environment in the eastern part of the Dnieper-Donets Basin during hydraulic fracturing was conducted for the first time, and a schematic model of tectonophysical changes in the geological environment as a result of hydraulic fracturing was constructed. Conclusion. The collectors of the West-Khrestyshche deposit are characterized by high petrophysical heterogeneity, where brittleness is determined by the ratio of quartz, carbonates, and clay. The most promising for effective hydraulic fracturing are sandstone horizons with balanced porosity, high brittleness, and moderate permeability. When designing hydraulic fracturing operations, it is advisable to consider the combined brittleness index, which combines both mineralogical and elastic parameters. In general, the most promising targets for hydraulic fracturing at the West-Khrestishche field are medium-grained quartz sandstones that combine high brittleness, sufficient porosity, and favorable thermobaric conditions.